Psychometric Properties and Measurement Invariance of the Childhood Trauma Questionnaire (Short Form) Across Genders, Time Points and Presence of Major Depressive Disorder Among Chinese Adolescents - Wang, Xin; Ding, Fengjiao; Cheng, Chang; He, Jiayue; Wang, Xiang; Yao, Shuqiao (Frontiers in Psychology, 2022)
Purpose: The Childhood Trauma Questionnaire-Short Form (CTQ-SF) is a widely used self-report tool designed to assess juveniles’ experiences of abuse and neglect. The current study examined the psychometric properties, particularly measurement invariance of the CTQ-SF in Chinese non-clinical adolescents and adolescents with major depressive disorder (MDD). Methods: Participants included 1,507 high school students (non-clinical sample) from Hunan Province and 281 adolescent patients with major depressive disorder (MDD sample) from The Second Xiangya Hospital. We examined the reliability and validity of CTQ-SF, confirm the five-factor model of the CTQ-SF. Multiple-group confirmatory factor analysis(CFA) was used to examine the measurement invariance across genders, presence of depression, and over time. Results: The CTQ-SF had good internal consistency in a non-clinical sample (Cronbach’s α=0.85) and MDD sample (Cronbach’s α=0.86). Good test-retest reliability (ICC=0.72) and Adequate validity were also observed. Good fit of the five-factor CTQ-SF model was confirmed in both samples. Multiple-group CFA confirmed that the CTQ-SF had the scalar invariance across genders and the presence of MDD, as well as over time. Conclusion: The CTQ-SF is an effective and reliable tool for assessing CM in Chinese adolescents(non-clinical sample and MDD sample). The results suggest that the horizontal and longitudinal invariance of CTQ-SF are strongly established, which means CTQ-SF can be meaningfully used to compare outcomes among Chinese adolescents (non-clinical sample and MDD sample). The experience of child maltreatment, especially neglect (emotional and physical), was found to be common in Chinese adolescents.